Executive Committee Minutes 2012-12-06 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 9/20 and 10/4 approved. Correspondence noted. Chair Report. Provost Report. Revision of the MA in Counseling approved for Senate consent calendar. Vice Chair Report. Revision to the CALS Multiple Subject teacher track approved for the Senate agenda. Resolution Reaffirming the Importance of Graduate Programs approved for the Senate agenda. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate Agenda approved.